2007
DOI: 10.1021/jp0683521
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Aluminum Location and Non-framework Ions Effects on Alkane Adsorption in Aluminosilicates:  A Molecular Simulation Study

Abstract: In our previous work, a computational method to characterize framework aluminum in aluminosilicates was proposed (García-Pérez, E., et al. Angew. Chem., Int. Ed. 2007, 46, 276). In this work, the method was adopted to identify the most likely positions of aluminum in TON, FER, and MOR zeolites and to understand their different adsorption behaviors in detail. The simulations show that the location of aluminum affects the positions of the ions, and thus influences the adsorption. With the determined structures, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 72 publications
2
45
0
Order By: Relevance
“…One could argue that such an empirical model may have very limited values if extended to other zeolites. In this respect it is encouraging that GarciaPerez and co-workers 122,123 showed that these potentials also work quite well for other zeolites (FER and TON).…”
Section: Cation-adsorbate Interactionsmentioning
confidence: 61%
See 1 more Smart Citation
“…One could argue that such an empirical model may have very limited values if extended to other zeolites. In this respect it is encouraging that GarciaPerez and co-workers 122,123 showed that these potentials also work quite well for other zeolites (FER and TON).…”
Section: Cation-adsorbate Interactionsmentioning
confidence: 61%
“…This suggestion in ref 206 was followed up by Liu and co-workers. 122,123,207 Liu et al showed that, with the united-atom force field of Dubbeldam et al, 94,97 which uses a σ CH 2 O ) 3.58 Å, an excellent agreement with the experimental data could be obtained. Interestingly, this agreement could only be obtained if the model included the effect of the acid sites in FER.…”
Section: Other Zeolitesmentioning
confidence: 90%
“…The framework of MOR consists of two distinct cavities, which are twelve membered main channels (7.0 × 6.5 A) in the direction of the z axis and eight membered side pockets (3.4 × 4.8Å) in y direction [38]. In N a-MOR, the adsorption of guest molecules is very sensitive to the distribution of aluminum atoms [59,60]. In our present study, we randomly distribute Al atoms over all tetrahedral sites of the N a-MOR supercell, in such a way that the Löwenstein rule as well as the guidelines outlined by Alberti et al [61] are satisfied.…”
Section: Micropores Of All-silica Zeolitesmentioning
confidence: 99%
“…Zeolites with a Si/Al ratio higher than 1 can be obtained from random substitution of aluminum by silicon, either ignoring [12,13] or taking into account distribution rules [14][15][16][17][18]. The aluminum atoms can also be assigned to energetic and entropic preferential positions [19][20][21][22][23][24], or using theoretical approaches that identifies experimentally accessible properties dependent on the aluminum distribution and associated cation distribution [25,26]. Substitution of silicon for aluminum generates a negative net charge in the zeolite framework that needs to be compensated by either nonframework protons or cations in order to make the zeolite charge neutral.…”
Section: Modeling Zeolites and Nonframework Cationsmentioning
confidence: 99%
“…Each substitution creates a negative charge in the framework that is compensated by a counterion or a proton. The location of these counterions influences the adsorption and the catalytic properties for these materials [25,26]. In addition, zeolites act as shape-selective catalysts with a high selectivity and reaction yield.…”
Section: Molecular Modeling Of Hydrocarbons In Zeolitesmentioning
confidence: 99%